Christian Feminist Theology in Pakistan - Ali, Farman (Feminist theology, 2022)
This study is an effort to determine the status of Christian feminist theology in Pakistan and discusses the issues and challenges of patriarchal control of Church and religious, political, social, and minority issues faced by Christian women in Pakistan. It traces the history of Christian feminist theology in Pakistan as well. This qualitative study looks at important texts written on Christian theology, Christian feminism, and history of Church in Pakistan and also presents findings of in-depth interviews with women associated with Church in Pakistan.